2022
DOI: 10.1038/s41558-022-01424-3
|View full text |Cite
|
Sign up to set email alerts
|

Poleward shift of Circumpolar Deep Water threatens the East Antarctic Ice Sheet

Abstract: Future sea-level rise (SLR) projections carry large uncertainties, mainly driven by the unknown response of the Antarctic Ice Sheet to climate change. During the past four decades, the contribution of the East Antarctic Ice Sheet to SLR has increased. However, unlike for West Antarctica, the causes of East Antarctic ice-mass loss remain largely unexplored. Here, using oceanographic observations off East Antarctica (80º-160ºE) we show that mid-depth Circumpolar Deep Water has warmed by 0.8-2.0°C along the conti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 39 publications
2
35
0
Order By: Relevance
“…The changes in glacial flow may reflect an increase in ocean heat transport to the base of the glacier and/or ice dynamics (i.e., ice tongue thinning, changes in ice tongue structure following calving, or release from pinning points) (Miles et al., 2021; Rignot et al., 2019). While changes in ocean heat transport cannot be assessed with available observations, recent studies have documented warming of waters off East Antarctica that may have increased ocean heat transport to the continental shelf (e.g., Herraiz‐Borreguero & Naveira Garabato, 2022; Yamazaki et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The changes in glacial flow may reflect an increase in ocean heat transport to the base of the glacier and/or ice dynamics (i.e., ice tongue thinning, changes in ice tongue structure following calving, or release from pinning points) (Miles et al., 2021; Rignot et al., 2019). While changes in ocean heat transport cannot be assessed with available observations, recent studies have documented warming of waters off East Antarctica that may have increased ocean heat transport to the continental shelf (e.g., Herraiz‐Borreguero & Naveira Garabato, 2022; Yamazaki et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The high basal melt rates close to the grounding line in this region of Antarctica have been linked to a warming of up to 0.5 • C over the last 40 years that occurred in the open ocean off East Antarctica, concurrent with an even more pronounced warming of 0.8-2 • C observed over the continental slope (Herraiz-Borreguero and Naveira Garabato, 2022). This Circumpolar Deep Water (CDW) warming is linked to a poleward shift of the Antarctic Circumpolar Current's southern extent into the Indian Ocean sector of the East Antarctic continental slope, in which the Shackleton system is located.…”
Section: Introductionmentioning
confidence: 95%
“…If grounding line retreat continues at the present rate, this retrograde slope will be reached within 100 years, raising the potential for MISI. With basal melt predicted to further inhibit the formation of DSW within the Vanderford polynya (Ribeiro et al, 2021;Herraiz-Borreguero & Garabato, 2022), mCDW intrusion may be enhanced, thereby providing the oceanic forcing required to drive further grounding line retreat. Although the dynamic response of Vanderford Glacier has been limited thus far, a consistent thinning trend was seen over the observational period, measured between -0.07 and -0.12 m yr -1 (2003-2017).…”
Section: Discussionmentioning
confidence: 99%
“…Ribeiro et al (2021) therefore suggested that a positive feedback may be initiated, whereby continued freshwater input from basal melt could hinder the formation of Dense Shelf Water (DSW) in the Vanderford polynya, thereby strengthening water column stratification and enabling the enhanced intrusion of warm mCDW at depth. Analysis by Herraiz-Borreguero & Garabato (2022) also suggests that this potential feedback may already be underway, with an observed decline in DSW concurrent with consistent sea ice production indicative of increased penetration of mCDW within the Vincennes Bay region. Whilst Vanderford Glacier is currently grounded on a prograde bedrock slope (Rignot et al, 2019), it overlies the Vanderford Trench, a deep subglacial trench characterised by an inland retrograde slope (Figure 1b) (Davis et al, 1986;Chen et al, 2011;Sun et al, 2016).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation